Analysis of Calcium (Ca) Levels in Milkfish’s (Chanos chanos) Bone Using Atomic Absorption Spectrophotometry (AAS) - Lia K. Dewi; Supriadi Supriadi; Siti Aminah (Jurnal Akademika Kimia, 2021)
Milkfish (Chanos chanos) is famous for Indonesian and has high economic value. Milkfish bone can be processed into flour. A milkfish bone sample was obtained from the Sioyong Market in Dampelas, Donggala. The purpose of this study was to determine the calcium (Ca) levels in milkfish bone using atomic absorption spectrophotometry (AAS). The sample preparation method used dry destruction with sample ignition. The results showed that the average calcium levels in the flesh and head bones of milkfish aged two months were 0.052 ± 0.0007% and 0.132 ± 0.0056%, while those at aged five months milkfish were 0.197 ± 0.0014% and 0.138 ± 0 0007%, respectively. This study concludes that the older the age of milkfish is, the higher the calcium levels in the bones.